Abril XI: Mes Internacional de la Fotografia 1995. - Ramírez, Luis Alfonso; Imagen Alterna, Merida (Mérida : Imagen Alterna, 1995)
Salas Portugal, Armando ; Burri, René ; Cruz, Marco Antonio ; Valtierra, Pedro ; Ortega, Raúl ; S., Hector García ; C., Efrén Mota ; Mendiola, Victor ; Castillo, Fernando ; Camacho, Gustavo ; Charpentier, Gilberto Chen ; Hallgren, Gunilla ; Andrade, Yolanda ; Almog, Lili ; Bois, Pascal ; Fischer, Gerardo ; et al.
Imagen Alterna, Merida, 1995
kunstcatalogus
Keywords: Mexico